Perovskite-perovskite laminated solar cell and preparation method and application thereof

By using additives such as quercetin and SnF2 in tin-lead perovskite films, the problem of Sn2+ oxidation and crystallization rates in Sn-Pb perovskite solar cells is solved, and the film quality and performance of the solar cell are significantly improved.

CN119855362APending Publication Date: 2025-04-18SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411943106.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The performance of Sn-Pb perovskite solar cells is affected by the problems of Sn2+ oxidation and fast crystallization rates, resulting in high defect density and low film quality, which limits the efficiency development and long-term stability of perovskite-perovskite stacked solar cells.

Method used

Quercetin is used as an additive for tin-lead perovskite films, and passivate the Sn and Pb vacancies through coordination, and combine SnF2 and tin powder to regulate film growth, inhibit Sn2+ oxidation, and optimize device performance.

Benefits of technology

It effectively reduces the defect density of the tin-lead perovskite film, improves the crystallization and film formation quality of the film, and improves the photoelectric conversion efficiency, open circuit voltage, fill factor and short circuit current density of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855362A_ABST
    Figure CN119855362A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite-perovskite laminated solar cell and a preparation method and application thereof. The invention discloses a brand new application field of quercetin, Sn < 2 + > can be inhibited from being oxidized into Sn < 4 + >, meanwhile, the reaction rate of SnI2 and FAI / MAI is slowed down, and the problems that Sn-Pb perovskite is low in crystal quality, high in defect density and the like are successfully solved. The quercetin can react with multiple components in the narrow-band-gap perovskite, Sn and Pb vacancy defects can be passivated through the coordination action and the action with uncoordinated Sn < 2 + > and Pb < 2 + >, and comprehensively, the quercetin can play a role in fully passivating defects in the narrow-band-gap perovskite, so that the crystallization and film forming quality of the narrow-band-gap perovskite is improved, and the defect density is reduced. The prepared tin-lead perovskite thin film is used for preparing a solar cell, and key technical parameters such as PCE, open-circuit voltage (VOC), fill factor (FF) and short-circuit current density (JSC) of a device can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite-perovskite tandem solar cell and a preparation method and application thereof. Background Art

[0002] Perovskite materials have attracted extensive attention from researchers due to their advantages such as high light absorption coefficient, low cost, adjustable optical band gap, and the ability to prepare flexible devices. After nearly a decade of development, the power conversion efficiency of single-cell perovskite solar cells has rapidly developed from the initial 3.8% to 26.54%, gradually approaching single-crystal silicon solar cells. However, for single-cell solar cells, their efficiency cannot break through the limit of the Shockley-Queisser (SQ) theoretical efficiency limit of 33.4%. In order to overcome the efficiency limitation of single-cell cells, a feasible method is to develop multi-junction stacked solar cells by combining two or more semiconductor light absorption layers with complementary band gaps, while reducing thermal losses and expanding the collection of the solar spectrum.

[0003] Perovskite materials can adjust the band gap through component engineering and are ideal materials for preparing perovskite-perovskite tandem cells. They provide a high-efficiency route for perovskite-perovskite tandem cells while maintaining the advantages of low-cost and low-temperature manufacturing, as well as the possibility of lightweighting the two sub-cells in the tandem cells and preparing flexible cells. Perovskite-perovskite tandem cells are usually composed of a narrow band gap (NBG, ~1.2 eV) cell at the bottom and a wide band gap (WBG, ~1.8 eV) cell at the top. Tin-lead (Sn-Pb) mixed perovskite as the narrow band gap part is an important component of perovskite-perovskite tandem cells. By partially introducing Sn into the lead-based perovskite 2+ It not only narrows the band gap but also alleviates the heavy metal toxicity problem caused by Pb. Although the highest efficiencies of single-junction Sn-Pb perovskite solar cells and perovskite-perovskite tandem cells have reached 24.5% and 30.1% respectively, achieving world-renowned achievements, compared with the current high-efficiency lead-based perovskite solar cells, Sn 2+ The introduction of Sn-Pb perovskites brings about various unavoidable problems that significantly affect the performance of battery devices. Two main factors lead to the high defect density and unnecessary non-radiative recombination of Sn-Pb perovskites: on the one hand, Sn-containing 2+ The perovskite film is easily corroded by oxygen in the air. 2+ Oxidized to Sn 4+ , resulting in serious p-type self-doping; on the other hand, SnI2 reacts faster with FAI / MAI than PbI2, and the crystallization rate of Sn perovskite is faster than that of Pb perovskite, making it difficult to prepare high-quality perovskite films. 2+The performance of Sn-Pb hybrid perovskite solar cells still lags behind that of pure Pb-based perovskite solar cells due to the problems of oxidation and crystallization rate. The performance limitation of Sn-Pb hybrid perovskite seriously affects the efficiency development and long-term stability of perovskite-perovskite tandem solar cells. Summary of the invention

[0004] The purpose of the present invention is to disclose a perovskite-perovskite tandem solar cell and a preparation method and application thereof, so as to solve one or more technical problems existing in the prior art and provide at least one beneficial option or create conditions.

[0005] The first aspect of the present invention is to provide the use of quercetin in the preparation of tin-lead perovskite thin films.

[0006] The second aspect of the present invention is to provide an additive used in preparing tin-lead perovskite thin films.

[0007] The third aspect of the present invention is to provide a method for preparing a tin-lead perovskite film.

[0008] A fourth aspect of the present invention is to provide a perovskite-perovskite tandem cell.

[0009] The application of the first aspect of the present invention refers to the ability of quercetin to react with uncoordinated Sn in the process of preparing tin-lead perovskite film through coordination. 2+ , Pb 2+ Interact with each other, thereby passivating Sn and Pb vacancy defects, improving the crystallization and film quality of Sn-lead perovskite films, and reducing defect density.

[0010] The structural formula of the quercetin is shown in formula (I).

[0011]

[0012] Formula (I) The tin-lead perovskite film additive in the second aspect of the present invention includes quercetin.

[0013] In a further application embodiment, the tin-lead perovskite film additive further includes SnF2 and / or tin powder. SnF2 can regulate the film growth and inhibit Sn 2+ Oxidation and optimization of device performance; tin powder can adjust the photoelectric properties of the film, catalyze reactions, and reduce Sn 4+ The combination of the three can reduce the surface roughness of the film and make the perovskite grains more complete.

[0014] The method for preparing the tin-lead perovskite film according to the third aspect of the present invention comprises the following steps: (1) preparing a precursor solution; (2) adding the tin-lead perovskite thin film additive to the precursor solution and continuously stirring; (3) After filtration, tin-lead perovskite film was obtained by spin coating.

[0015] In a further application embodiment, in step (1), the chemical formula of the precursor solution includes Cs 0.1 FA 0.6 MA 0.3 Sn 0.5 Pb 0.5 I3 or FA 0.7 MA 0.3 Sn 0.5 Pb 0.5 At least one of I3.

[0016] In a further application embodiment, in step (1), the solvent of the precursor solution is a mixture of DMF and DMSO; preferably, the volume ratio of DMF to DMSO is (3-4):1.

[0017] In a further application embodiment, the tin-lead perovskite film additive includes SnF2, tin powder and quercetin.

[0018] In a further application implementation, the process of adding the tin-lead perovskite film additive in step (2) is: first add SnF2 and tin powder to the precursor solution, stir at room temperature for more than 2 hours, and then add quercetin and stir for at least 1 hour.

[0019] In a further application embodiment, the filtering in step (3) is to remove tin powder through a 0.22 μm PTFE filter.

[0020] In a further application embodiment, the concentration of quercetin is 2.0-6.0 mg / mL; preferably, the concentration of SnF2 is 10 mol; preferably, the concentration of tin powder is 4.0-5.0 mg / mL.

[0021] The perovskite-perovskite stacked cell described in the fourth aspect of the present invention comprises an electrode substrate, a wide-bandgap sub-cell and a narrow-bandgap sub-cell, wherein the narrow-bandgap sub-cell contains a tin-lead perovskite film prepared by the preparation method described in the third aspect of the present invention.

[0022] In a further application implementation manner, an interconnecting intermediate layer is further provided between the wide bandgap sub-cell and the narrow bandgap sub-cell.

[0023] In a further application embodiment, the method for preparing the perovskite-perovskite tandem cell comprises the following steps: S1, sequentially preparing a hole transport material I and a wide bandgap perovskite layer on an electrode substrate; S2, evaporating electron transport materials by physical vapor deposition; S3, depositing an interconnect intermediate layer by an atomic layer deposition system; S4, preparing a hole transport material II and the tin-lead perovskite film on the interconnect intermediate layer; S5. Evaporating electron transport materials and metal electrodes by physical vapor deposition.

[0024] The beneficial effects of the present invention are: providing a new use of quercetin, which can be used as an additive for preparing tin-lead perovskite film to inhibit Sn 2+ Oxidized to Sn 4+ , and at the same time slowed down the reaction rate of SnI2 and FAI / MAI, successfully solving the problems of low crystal quality and high defect density of Sn-Pb perovskite. The quercetin can interact with various components in narrow bandgap perovskite, and can react with uncoordinated Sn through coordination. 2+ , Pb 2+ The vacancy defects of Sn and Pb can be passivated by quercetin. + , M.A. + The nitrogen atoms in the quercetin form hydrogen bonds to passivate FA and MA vacancy defects. In summary, quercetin can play a role in full defect passivation in narrow-bandgap perovskites, thereby improving the crystallization and film quality of narrow-bandgap perovskites and reducing defect density. The prepared tin-lead perovskite film is used to prepare solar cells, which can effectively improve the device PCE and open circuit voltage ( V OC )、fill factor(FF)、short circuit current density( J SC ) and other key technical parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a schematic structural diagram of the perovskite-perovskite tandem battery described in Example 3; Figure 2 is a JV curve diagram of the volt-ampere characteristic test experiment in Example 4; Figure 3 is a scanning electron microscope image of Example 4; Figure 4 is an atomic force microscope image of Example 4; Figure 5 This is the X-ray diffraction pattern of Example 4. DETAILED DESCRIPTION

[0026] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all belong to the scope of the present invention.

[0027] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0028] Example 1: Preparation of a No. 1 narrow bandgap battery.

[0029] The No. 1 narrow bandgap battery is based on a trans-structure, and includes an indium tin oxide (ITO) glass electrode substrate, a hole transport material layer (PEDOT:PSS), a Sn-Pb perovskite film (NBG, 1.25 eV), an electron transport layer (C 60 / BCP) and copper electrodes.

[0030] (1) Prepare a perovskite precursor solution with a band gap of 1.25 eV. The components are shown in Table 1.

[0031] Table 1

[0032] According to the ratio shown in Table 1, FAI, MAI, SnI2 and PbI2 were mixed in a solvent consisting of DMF and DMSO, SnF2 and tin powder were added and stirred at room temperature for 2 hours, and then quercetin was added and stirred for another hour for use; before use, the tin powder needed to be removed through a 0.22 μm PTFE filter.

[0033] (2) The narrow bandgap battery preparation process: (2-1) The ITO glass electrode substrate (resistivity 10 Ω / sq, size 1.5×1.5 cm, purchased from Advanced Election Technology Co., Ltd.) was cleaned in an ultrasonic cleaner with deionized water, acetone and ethanol for 20 to 30 minutes respectively.

[0034] (2-2) Dry the ITO glass electrode substrate and expose it in a UV-ozone cleaning machine for 20 to 25 minutes to improve its wettability.

[0035] (2-3) PEDOT:PSS was filtered through a 0.22 μm PES filter, and then 50-60 μL of the solution was statically spin-coated on an ITO glass electrode substrate at 4000 rpm for 30 seconds, followed by annealing at 140-150 °C in air for 15-20 minutes.

[0036] (2-4) 50 μL of the pre-prepared and filtered perovskite precursor solution was added to the hole transport material layer using a two-step spin coating process, first at 1000 rpm for 10 seconds and then at 5000 rpm for 40 seconds. Within 18 to 20 seconds before the end of high-speed spin coating, 180 μL of chlorobenzene (CB, used as an anti-solvent) was quickly added to the film surface within 1 second. The wet film was moved to a heating stage and annealed at 100 °C for 10 minutes.

[0037] (2-5) The Sn-Pb perovskite film was passivated with 50~80 μL of 4-(trifluoromethyl)benzoylhydrazide (TFH) solution (dissolved in isopropanol, concentration of 3 mg / mL) at 5000 rpm for 30 seconds, and then annealed at 80 °C for 2 minutes.

[0038] (2-6), in 4×10 -5 Torr pressure, and the evaporation rate was 0.2~0.5 Å / s to prepare 40~45 nm C 60 , and 8 nm BCP was prepared by thermal evaporation at an evaporation rate of 0.1~0.2 Å / s as an electron transport layer; and 100 nm copper electrode was prepared by thermal evaporation at an evaporation rate of 1.0~1.5Å / s.

[0039] Example 2: Preparation of a second narrow bandgap battery.

[0040] The second narrow bandgap battery is basically the same as the first narrow bandgap battery, and the difference lies in the difference in the components of the perovskite precursor solution. The specific components of the perovskite precursor solution are shown in Table 2.

[0041] Table 2

[0042] The preparation process is the same as that of Example 1.

[0043] Example 3: Preparation of perovskite-perovskite tandem cells.

[0044] The perovskite-perovskite stacked cell is also based on a trans-structure and consists of an electrode substrate, a wide-bandgap subcell, and a narrow-bandgap subcell. The specific structure includes: an indium tin oxide (ITO) glass electrode substrate, a hole transport material layer I (MeO-PACz), a wide-bandgap perovskite film (1.79 eV), an electron transport layer I (C 60 )、interconnection intermediate layer (SnO2), hole transport material layer II (PEDOT:PSS), Sn-Pb perovskite film (1.25 eV), electron transport layer II (C 60 / BCP) and copper electrodes.

[0045] (1) The preparation process of the perovskite-perovskite tandem battery: (1-1) Clean the ITO glass electrode substrate with deionized water, acetone and ethanol in an ultrasonic cleaner for 20 to 30 minutes respectively.

[0046] (1-2) Dry the ITO glass electrode substrate and expose it in a UV-ozone cleaner for 20 to 25 minutes to improve its wettability.

[0047] (1-3) MeO-2PACz (dissolved in isopropanol, concentration of 0.3 mg / mL) was spin coated on the ITO substrate at 5000 rpm for 30 seconds and then annealed at 100 °C for 10 minutes.

[0048] (1-4) Add 1.2 mol / L Cs 0.2 FA 0.8 Pb(I 0.6 Br 0.4 )3 The wide bandgap perovskite precursor solution was spin-coated on the hole transport material layer I at a speed of 1000 rpm for 5 seconds, and then spin-coated at a speed of 3000 rpm for 40 seconds. Within 20 seconds before the end of the high-speed spin coating, 180 μL of chlorobenzene (CB, used as an anti-solvent) was quickly added to the film surface within 1 second. The wet wide bandgap perovskite film was annealed at 100 °C for 15 minutes.

[0049] (1-5) 80 μL of PDI (dissolved in IPA, concentration of 1 mg / mL) was dripped onto the cooled film at a speed of 5000 rpm for 30 seconds, and then annealed at 100 °C for 5 minutes.

[0050] (1-6), in 4×10 -5 Torr pressure, and the evaporation rate was 0.2 Å / s to prepare 40~45 nm C 60 .

[0051] (1-7) In the ALD system, 20 nm SnO2 is deposited at about 100 °C as the interconnect intermediate layer.

[0052] (1-8) Through thermal evaporation, a 1.5 nm layer of gold (Au) is covered on the interconnect intermediate layer to increase conductivity.

[0053] (1-9) PEDOT:PSS was filtered through a 0.22 μm PES filter, and then 100 μL of the solution was statically spin-coated on the interconnect interlayer at 4000 rpm, followed by annealing at 100 °C in air for 25 min.

[0054] (1-10) Take the perovskite precursor solution prepared in Example 1 and filter it, then drop 50 μL onto the hole transport material layer II, and use a two-step spin coating process, first spin coating at 1000 rpm for 10 seconds, and then spin coating at 5000 rpm for 40 seconds. Within 18 to 20 seconds before the end of high-speed spin coating, quickly drop 180 μL of chlorobenzene (CB, used as an anti-solvent) onto the film surface within 1 second. Move the wet film to a heating table and anneal at 100°C for 10 minutes.

[0055] (1-11) The Sn-Pb perovskite film was passivated with 50~80 μL of TFH solution (dissolved in isopropanol, concentration of 3 mg / mL) at 5000 rpm for 30 seconds and then annealed at 80 °C for 2 minutes.

[0056] (1-12), in 4×10 -5 Torr pressure, and the evaporation rate was 0.2~0.5 Å / s to prepare 40~45 nm C 60 , and 8 nm BCP was prepared by thermal evaporation at an evaporation rate of 0.1~0.2 Å / s as electron transport layer II; a 100 nm copper electrode was prepared by thermal evaporation at an evaporation rate of 1.0~1.5 Å / s.

[0057] The structural schematic diagram of the prepared perovskite-perovskite stacked battery is as follows Figure 1 shown.

[0058] Example 4: Sn-Pb perovskite film control experiment.

[0059] The Sn-Pb perovskite thin film prepared by the configuration and film forming method described in Example 1 is denoted as the verification group (Target).

[0060] A 1.25 eV bandgap perovskite precursor solution without quercetin was prepared, and its composition was basically the same as that in Table 1, except that it did not contain quercetin, and the steps of adding and stirring quercetin were omitted in the preparation process. The prepared Sn-Pb perovskite film was used as a control group (Control).

[0061] From the scanning electron microscopy images (such as Figure 2 ) and atomic force microscopy images (as shown Figure 3 As shown in the figure, it can be observed that after the quercetin treatment, the Target group significantly improved the microstructure of the narrow bandgap perovskite, the surface roughness of the film was significantly reduced, and the perovskite grains were more complete. Figure 4 The enhancement of the diffraction intensity in the α-D phase (as shown) can explain the improvement of the crystallinity of the narrow-bandgap perovskite.

[0062] Example 5: Control experiment of perovskite-perovskite tandem cells.

[0063] The perovskite-perovskite tandem cell prepared in Example 3 was taken as the verification group (Target).

[0064] A 1.25 eV bandgap perovskite precursor solution without quercetin was prepared, and its composition was basically the same as that in Table 1, except that it did not contain quercetin, and the steps of adding and stirring quercetin were omitted in the preparation process. A perovskite-perovskite stacked cell was prepared according to the steps provided in Example 3, and was recorded as a control group (Control).

[0065] Determined by volt-ampere characteristic test experiment JV Curve like Figure 5 As shown. It can be observed that the photoelectric conversion efficiency (PCE) of the Target group is 29.18%, which is much higher than the 26.14% of the Control group; and the fill factor (FF) of the Target group is higher, which means that it has less loss in the energy conversion process and can convert light energy into electrical energy more efficiently; the short-circuit current density ( J SC ) is 16.32 mA / cm 2 , which is also higher than the 15.58 mA / cm in the Control group. 2 , reflecting that the batteries of the Target group can output higher current density under short-circuit state, which is conducive to achieving higher current output in practical applications.

[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. Application of quercetin in the preparation of tin-lead perovskite films.

2. A tin-lead perovskite film additive, characterized in that: Includes quercetin.

3. The tin-lead perovskite thin film additive according to claim 2, characterized in that: Also included is SnF2 and / or tin powder.

4. A method for preparing a tin-lead perovskite film, characterized in that: Includes steps: (1) preparing a precursor solution; (2) adding the tin-lead perovskite thin film additive according to claim 2 or 3 to the precursor solution and continuously stirring; (3) After filtration, tin-lead perovskite film was obtained by spin coating.

5. The preparation method according to claim 4, characterized in that: In step (1), the chemical formula of the precursor solution includes Cs 0.1 FA 0.6 MA 0.3 Sn 0.5 Pb 0.5 I3 or FA 0.7 MA 0.3 Sn 0.5 Pb 0.5 At least one of I3.

6. The preparation method according to claim 4, characterized in that: The tin-lead perovskite film additive comprises SnF2, tin powder and quercetin; the process of adding the tin-lead perovskite film additive in step (2) is: firstly add SnF2 and tin powder to the precursor solution, stir at room temperature for more than 2 hours, then add quercetin and stir for at least 1 hour.

7. The preparation method according to claim 6, characterized in that: The concentration of the quercetin is 2.0-6.0 mg / mL; preferably, the concentration of the SnF2 is 10 mol; preferably, the concentration of the tin powder is 4.0-5.0 mg / mL.

8. The preparation method according to claim 4, characterized in that: The solvent of the precursor solution is a mixture of DMF and DMSO; preferably, the ratio of DMF to DMSO in the organic solvent is (3-4):

1.

9. A perovskite-perovskite tandem battery, characterized in that: The invention comprises an electrode substrate, a wide bandgap sub-battery and a narrow bandgap sub-battery, wherein the narrow bandgap sub-battery contains a tin-lead perovskite film prepared by the preparation method according to any one of claims 4 to 8.

10. The perovskite-perovskite tandem cell according to claim 9, characterized in that: An interconnecting intermediate layer is also provided between the wide bandgap sub-cell and the narrow bandgap sub-cell.

Citation Information

Patent Citations

  • Lead-free tin-based halide perovskite thin film, composition for preparation, preparation method and application

    CN115286939A

  • Hydrazine monohydrochloride-doped perovskite material, preparation method thereof and perovskite solar cell

    CN118251107A

  • Anti-solvent-free all-perovskite laminated solar cell and preparation method and application thereof

    CN118574431A